Accurate Retrieval of Asymmetry Parameter for Large and Complex Ice Crystals From In‐Situ Polar Nephelometer Measurements. Issue 3 (10th February 2022) - Xu, Guanglang; Schnaiter, Martin; Järvinen, Emma
Abstract: The retrieval of the asymmetry parameter from nephelometer measurements can be challenging due to the inability to detect the whole angular range. Here, we present a new method for retrieving the asymmetry parameter of ice crystals with relatively large size parameters (>50) from polar nephelometer measurements. We propose to fit the angular scattering measurement with a series of Legendre polynomials and the best fitted coefficients give the asymmetry parameter. The accuracy of the retrieval is analyzed by accessing the smoothness of the phase function, which is closely linked to the complexity of ice particle. It is found that the uncertainty of retrieval could be smaller than 0.01, provided the measured intensity profile is smooth enough. As an application, we report an case study on Arctic cirrus, which shows a mean value for the asymmetry parameter of 0.72. Plain Language Summary: The asymmetry parameter of ice crystals is a parameter that can largely determine cirrus cloud's interaction with solar radiation energy, and therefore its magnitude is important for climate and weather prediction models. In‐situ measurements using nephelometers is a direct way to measure partial angular scattering functions, and the accuracy of these measurements is of upmost importance. In this paper, we report a novel method for retrieving the asymmetry parameter from polar nephelometer measurements. Depending on the smoothness of the measured angular scattering function, the accuracy of the retrieval could be very high. We report a case study over the Arctic region, showing a low asymmetry parameter around 0.72. Key Points: A new algorithm is developed for retrieving the asymmetry parameter of large and complex ice crystals from polar nephelometer measurements Accuracy of retrieval could be better than 0.01, provided sufficient smoothness of the phase function A case study of Arctic cirrus measurement during the CIRRUS‐HL campaign is reported